Mobilizing P2P Diffusion for New Agricultural Practices: Experimental Evidence from Bangladesh. (11th May 2021) - Fafchamps, Marcel; Islam, Asad; Malek, Abdul; Pakrashi, Debayan
Abstract: This paper uses a randomized controlled experiment in which farmers trained on a new rice cultivation method teach two other farmers. The results show that the intervention increases yields and farm profits among treated farmers. Teacher-trainees are effective at spreading knowledge and inducing adoption relative to just training. Incentivizing teacher-trainees improves knowledge transmission but not adoption. Matching teacher-trainees with farmers who list them as role models does not improve knowledge transmission and may hurt adoption. Using mediation analysis, the study finds that the knowledge of the teacher-trainee is correlated with that of their students, consistent with knowledge transmission. The paper also finds that systems of rice intensification (SRI) knowledge predicts adoption of some SRI practices, and that adoption by teacher-trainees predicts adoption by their students, suggesting that students follow the example of their teacher. With cost-benefit estimates of social returns in excess of 100 percent, explicitly mobilizing peer-to-peer (P2P) transmission of knowledge seems a cost-effective way of inducing the adoption of new profitable agricultural practices.